(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The laudable objectives of entrepreneurship education have not been achieved because of the chunk of graduates unemployed, seemingly due to lack of requisite skills for employment in modern offices. This problem prompted this study to investigate funding-related administrative impediments to the effective implementation of entrepreneurship education programme in universities insouth-east Nigeria. One research questions guided the study while two null hypotheses were formulated. The study adopted a descriptive survey research design. The entire population of 79 administrative staff of entrepreneurship development centres in universities in South East, Nigeria was used for data collection. Questionnaire was used to collect data. The questionnaire was validated by three experts, and its internal consistency yielded a co-efficient value of 0.79 using Cronbach Alpha Method was obtained. Mean and standard deviation was used to answer the research questions while t-Test was used to test the null hypotheses at 0.05 level of significance. Findings revealed that administrative staff of entrepreneurship development centres agreed on funding-related administrative impediments to the effective implementation of the entrepreneurship education programme in universities in South East Nigeria.